Pediatric internal carotid artery dissection and stroke after minor head injury - Daniel Kemple; Hanna Knauss; Kayleene Pagan Correa; Alyse Stolting (Journal of the American College of Emergency Physicians Open)
Abstract Pediatric arterial ischemic stroke (AIS) is an important cause of juvenile brain injury. There are no well‐established guidelines for universal management of childhood stroke. Although cerebral arteriopathies are the most common cause of pediatric AIS, head or neck trauma is an established risk factor.1 We report the case of a 6‐year‐old African American male who presented to the pediatric emergency department with aphasia and right‐sided hemiparesis 4 days after a fall in gym class. Magnetic resonance angiography showed tandem occlusion of the left internal carotid artery (ICA) and middle cerebral artery. During endovascular exploration for thrombectomy, a dissection of the ICA also was discovered and recanalized. Following neurointerventional embolectomy, the patient sustained full neurologic recovery without recurrence at 2 years. The safety and efficacy of therapeutic embolectomy in children is not well documented and warrants additional discussion for establishing novel protocols.